Axially symmetric dual‐reflectarray antennas. Issue 13 (1st June 2014) - Yoon, Ji Hwan; Yoon, Young Joong; Lee, Woo‐sang; So, Joon‐ho
Abstract : An axially symmetric dual‐reflectarray antenna is proposed. A main reflectarray is designed to mimic a paraboloidal main reflector, and a sub‐reflectarray is designed to mimic a hyperboloidal or an ellipsoidal sub‐reflector. The dual‐reflectarray antenna is more compact than the conventional curved dual reflector. The dual‐reflectarray antenna is designed at W‐band and compared with its equivalent Cassegrain antenna.